2021
DOI: 10.1080/09575146.2021.1940876
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public and private preschool teachers’ beliefs and practices regarding gifted children from three to six years old in Riyadh, Saudi Arabia

Abstract: To cite this article: Dimah Hamad Aldosari (2021): Exploring public and private preschool teachers' beliefs and practices regarding gifted children from three to six years old in Riyadh, Saudi Arabia, Early Years,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Aldosari [19] aimed to explore private and public pre-school teachers' perceptions and practices toward gifted children aged 3 to 6 in Riyadh, the Kingdom of Saudi Arabia. A quantitative study indicated that Saudi Arabian private and public pre-school teachers believe children who are gifted have a higher cognitive ability level than their classmates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aldosari [19] aimed to explore private and public pre-school teachers' perceptions and practices toward gifted children aged 3 to 6 in Riyadh, the Kingdom of Saudi Arabia. A quantitative study indicated that Saudi Arabian private and public pre-school teachers believe children who are gifted have a higher cognitive ability level than their classmates.…”
Section: Literature Reviewmentioning
confidence: 99%